HUBUNGAN SIKAP BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI GUGUS IV KECAMATAN LIMAPULUH KOTA PEKANBARU - Ihsani, Dara Aulia; Kurniaman, Otang; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the problems that have been observed before doing research can be seen that the attitude of learning is very supportive to the implementation of good teaching and learning process. The purpose of this research to find out the correlation of learning attitude and outcomes of student’s mathematics learning fifth grade in state primary school cluster IV Limapuluh District Pekanbaru City. This research using correlational method. The sampling using simple random sampling technique. Methods of data collection using questionnaires and documentations of the value of mid second semester. The analysis technique using product moment. Requirements analysis test in the form of normality and linearity test. Analysis test and requirements analysis test using SPSS 20. Results of research is conducted show that there is a correlation between learning attitude and outcomes of student’s mathematics learning fifth grade in state primary school cluster IV Limapuluh District Pekanbaru City obtained rxy of 0.321 with a low level of correlation and also the attitude of learning to give effect to the results learning that is equal to 10.3%. t test values obtained significantly by 0.528 and greater than α which is 0.05 this shows that there is a significant correlation between learning attitude and outcomes of student’s mathematics learning fifth grade in state primary school cluster IV Limapuluh District Pekanbaru City.Key words: Learning attitude, outcomes of student’s mathematics learning